Sheep Meat Cultivation in the Foothills of Uzbekistan - Klichev Zafar Safarovich; Saydullaeva Shoira; Saidullaev Zoir (Research Parks Publishing LLC, 2022)
This article describes the results of scientific researches and methods of sheep meat cultivation in the foothills of Uzbekistan.